A observação da estrutura textual de livros e sua contribuição para a catalogação de assuntos em bibliotecas universitárias da UNESP - Reis, Daniela Majorie dos [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2010)
The indexing is a kind of description whose aim is to establish concepts expressed in a document and representing them according to a documentary language. There are elements that can contribute to a more complete selection of terms that will represent the document, like the observation of its textual structure and the context where the indexing professional acts. The analysis of the book textual structure can be carried out in a way that facilitates the indexing, as the professional can foresee the parts of the text where he localizes and identifies the more representative terms of the textual content. In such a way, it is intended to comprehend and inquire, with the applying of Verbal Protocol, the use that São Paulo libraries indexers do from the textual structure during the determination of subjects in such a way as to obtain the disclosure of their procedures, difficulties and restrictions through the externalization of thoughts during the recording of the indexing task. From the data analysis, it was possible to find out that the right hand page, the back of the title page, the chapters and other parts of the book s structure provided the greater number of terms, becoming the most important ones for the indexing task.

La indexación es una forma de descripción que busca determinar conceptos expresos en un documento y representarlos de acuerdo con un lenguaje documental. Existen factores que pueden contribuir para una selección más completa de los términos que representarán el documento, tales como la observación de su estructura textual y el contexto de actuación profesional del indexador. El análisis de la estructura textual del libro puede ser realizada de una forma que facilite la indexación, pues el profesional puede preconocer las partes del texto en que localiza e identifica los términos más representativos del contenido textual. De esta forma, se busca comprender e investigar, con la aplicación del Protocolo Verbal, el uso que el indexador de bibliotecas de São Paulo realiza de la estructura textual durante la determinación de asuntos, de manera que se pueda obtener la revelación de sus procedimientos, dificultades y restricciones mediante la exteriorización de pensamientos durante la grabación de la indexación. A partir del análisis de los datos fue posible constatar que el anverso de la hoja de portada, dorso de la hoja de portada, desenvolvimiento (capítulos), entre otras partes de la estructura del libro proporcionarán la determinación del mayor número de términos, tornándolas más importantes para la indexación.
The contribution of the observation of the textual structure of books to subject cataloguing: a case study in the UNESP university libraries
La observación de la estructura textual de los libros para la catalogación de matérias en las bibliotecas universitárias de la UNESP
Keywords: indexação; biblioteca universitária; protocolo verbal